Recycling zeolitic tuff and marble waste in the production of eco-friendly geopolymer concretes. (20th September 2020) - Tekin, Ilker; Gencel, Osman; Gholampour, Aliakbar; Oren, Osman Hulusi; Koksal, Fuat; Ozbakkaloglu, Togay
Abstract: The use of waste-based materials as cement alternative in concrete has recently received significant attention for the development of an eco-friendly construction material. The aim of the study reported in this paper is to develop a sustainable composite using waste products and natural fibers to reduce the environmental impact associated with cement production and extraction of non-renewable natural aggregates. Therefore, in this paper, an experimental study on the properties of alkali-activated composite that was manufactured with zeolitic tuff and marble waste is presented. Cotton and viscon fibers were also added to the composites to investigate the effect of crack bridging on the behavior of natural fiber-reinforced geopolymer composites with 5 M and 10 M sodium hydroxide (NaOH). The results show that geopolymers prepared with 10 M NaOH exhibit a higher compressive strength (53–371% at 28 days), elastic modulus (25–343% at 28 days), dry density (2–13%), and thermal conductivity (1–20%), a lower water absorption (1–35% at 28 days) and apparent porosity (1–30%), and a nearly similar flexural strength compared to those prepared with 5 M NaOH. It is also found that viscon fiber-reinforced geopolymers experience a higher compressive strength, elastic modulus and thermal conductivity, but a lower dry density than cotton fiber-reinforced geopolymers. These results are promising and point to the significant potential of the simultaneous use of zeolitic tuff and marble waste as cement replacements together with natural fibers as crack bridging material to develop an eco-friendly composite, which contributes toward reducing the carbon dioxide emission associated with the cement production and eliminating the environmental effect of abundant waste-based materials. Highlights: Zeolitic tuff and marble waste are used as cement replacements in geopolymers. Influence of the addition of cotton and viscon fibers is studied on properties of geopolymer. 10 M NaOH geopolymers exhibit higher strength and lower water absorption than 5 M NaOH geopolymers. Geopolymer with viscon fiber has higher strength and thermal conductivity than that with cotton fiber. 5 M NaOH geopolymer with 1.5% viscon fiber has comparable properties to the control geopolymer.